Phenotypic, molecular and mating type analyses of Exserohilum rostratum associated with leaf spots of rice - Kusai, Nor Azizah (2015)
Exserohilum rostratum is one of the plant pathogens causing leaf spot disease, which affects wide range of plant species, mainly grasses. There has been no report of E. rostratum causes the disease on rice plant particularly on leaves, therefore this study was conducted. During a series of sampling in March to August 2013, leaf spot is one of common symptoms found in rice plantations in Malaysia. The objectives of this study were to identify fungi isolated from leaf spot of rice based on phenotypic and molecular approaches, to determine whether or not E. rostratum isolates were pathogenic, to analyze the mating type of E. rostratum using Polymerase Chain Reaction (PCR) and to examine the sexual development of E. rostratum isolates. All isolated fungi were purified and identified based on their phenotypic features for species delimitation and confirmed by sequencing the internal transcribed spacers (ITS) region. Seventy-eight isolates were identified; E. rostratum (45 isolates), Bipolaris sorokiniana (10 isolates), Curvularia hawaiiensis (8 isolates), C. geniculata (6 isolates), C. eragrostidis (6 isolates), C. aeria (2 isolates) and C. lunata (1 isolate). A phylogenetic tree was constructed using neighbor-joining method showed the same species grouped in the same clade. Clade I consisted of E. rostratum while Clade II were Bipolaris sorokiniana and Curvularia species. Based on pathogenicity test, some isolates of E. rostratum were pathogenic and produced leaf spot symptoms towards rice. In this study, E. rostratum is minor or secondary pathogen to rice because it showed smaller lesion compared to infection by B. oryzae, the main pathogen of brown spot disease. Mating type (MAT) of all isolates of E. rostratum were amplified using two sets of primers (NM162MAT1_1F1Seto and NM163MAT1_1R1Seto for MAT1-1; NM164MAT1_2F1Seto and NM165MAT1_2R1Seto for MAT1-2). Three isolates were confirmed carried MAT1-1 allele while 42 isolates are MAT1-2 isolates. The imbalance distribution of both MAT may caused by ratio of modes of reproduction and selection pressure in the field. The opposite MAT isolates were crossed on Sach’s medium for 3 weeks in quadruplicate. Nine isolates were indicated as fertile, which produced mature pseudothecia and ascospores, 12 isolates produced barren pseudothecia (empty asci) and the remaining 24 isolates were non-fertile without formation of pseudothecia. Three isolates of E. rostratum from this study; one MAT1-1 isolate (UPM1109) and two isolates of MAT1-2 (UPM1247 and UPM1152) are highly fertile and suggested to be used as tester strains. The developed tester strains may facilitate other researchers to access the fertility on other related study on other E. rostratum isolates.